Analisis Perbandingan Tingkat Literasi Membaca dan Menyimak Intensif Mahasiswa Semester Awal - Habiburrahman, Lalu; Harisanti, Baiq Muli (Educatoria : Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study compared the listening and intensive reading abilities of early semester students, Mandalika University of Education (n=43) through a descriptive phenomenological approach. The research instruments consisted of the video "AI Domination War" (13 minutes 14 seconds) for listening, and the literary text "Permenungan dan Pengapungan" for intensive reading. The results showed a significant disparity between the two abilities. The average score for listening (93) was higher than reading (73). As many as 93.02% of the sample (40 people) reached the high category in listening, while in intensive reading only 53.49% (23 people) were included in the high category. Further analysis revealed that students were able to process simple information from both media, the main difficulty arose in processing complex texts, especially with non-linear narrative structures, and as many as 30.23% of respondents (13 people) were in the low category for intensive reading. These findings were supported by triangulation analysis through observation, assignment documents, and teaching materials. The study concluded that audiovisual listening abilities were more dominant than text literacy, and complex literary texts were the main challenge for students. The implications of the study emphasize the importance of developing a learning model that balances listening and reading competencies, especially in dealing with literary and structurally complex texts in an academic environment. This finding is relevant to the development of literacy curricula in Higher Education in the digital era.